Evaluation of different types of phytoplankton on rearing of vannamei shrimp larva (Litopenaues vanamei) - Ratnawati, Ratnawati; Alimin, Ilham; Hasan, Subakti (Acta Aquatica: Aquatic Sciences Journal, 2022)
This study aims to determine the effect of giving different types of phytoplankton to the survival, abundance of bacteria and water quality of white shrimp (Litopenaeus vannamei). This research was carried out from October to November 2020 at the Laboratory of the Brackish Water Cultivation Center (BBAP) Ujung Batee, Aceh Besar. The larvae of the tested shrimp used were shrimp at Nauplius stage 5-6. The method used was a Completely Randomized Factorial Design (CRD) with 5 treatments and 4 replications. Provision of phytoplankton Thalassiosira sp and artificial feed (treatment A), Chaetoceros sp and artificial feed (treatment B), Skeletonema costatum (Treatment C), a combination of phytoplankton Thallasiosira sp, Chaetoceros sp, Skeletonema costatum and artificial feed (treatment D) and artificial feed alone (treatment E). The test larvae were placed in a container with a density of seed stocking for each container was 100 fish/liter with a maintenance period of up to Post larval stage 1 (PL 1). The frequency of giving phytoplankton was done 2 times a day, namely at 09.00 am and 15.00 pm. While the frequency of artificial feed was 6 times, namely at 07.00 WIB in the morning, 11.00 WIB, 16.00 WIB in the afternoon, 21.00 WIB at night, 01.00 WIB in the morning and 04.00 WIB in the morning. The results obtained showed that the treatment with phytoplankton had a significant effect on the survival of vaname shrimp larvae. Therefore, it can be concluded that the highest survival rate is in treatment D.Keywords: phytoplankton; survival; vaname; water quality